Water Quality and Soil Properties Water Quality and its Effect on the Properties of Light Textured Soils - Lal, P; Lal, F (Annals of Arid Zone, 2016)
Forty seven water samples and an equal number of corresponding soil samples were analysed for different constituents. Almost all the soils were sandy or loamy sand in texture. Results show that the majority of waters belong to high salinity and high sodium category according to U.S. Salinity Laboratory classification. The potential salinity and residual sodium carbonate are also high as per limits suggested by Doneen (1966) for the former and Eaton (1950) for the latter. Significant positive coefficients of correlations were found between both EC and potential salinity of irrigation water and EC of saturation extract of the irrigated soils. Similarly, significant positive coefficients of correlations were obtained between SAR and residual sodium carbonate of the water and ESP of the irrigated soils as well as the boron content of waters and water soluble boron in respective soils. The hydraulic conductivity of irrigated soils was negatively correlated. with the permeability index of water. In general the EC of saturation extract and the water soluble boron in irrigated soils were 63.6 and 60.0 per cent of the EC and boron content of water respectively. The need for working out the suitable standards for judging the suitability of irrigation water for its use on light textured permeable soils has been emphasized.